Peran Kepemimpinan Visioner Kepala Sekolah Dalam Peningkatan Mutu Pengelolaan Sekolah Di SMA Swasta Dharma Bhakti Siborongborong Tahun 2023 - Sulastri Lumban Gaol; Robinhot Sihombing; Endang Juliati Manullang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was conducted to find out the role of the principal's visionary leadership in improving the quality of school management at Dharma Bhakti Siborongborong Private High School. The research method used is a qualitative descriptive method with a case study plan and data collection from informants using snowball sampling techniques through interviews, observation and documentation. The qualitative data obtained will be analyzed through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the principal of Dharma Bhakti Siborongborong Private High School is able to carry out the visionary leadership role, namely as a direction setter, agent of change, spokesperson and trainer in managing the school. This research concludes that to realize mutual school management, the visionary leadership role of the school principal is needed by communicating the vision and directing all school members to remain focused on the vision that has been set, making the school that is experiencing change better and persisting to make the school superior, conveying ideas. - the idea is through joint meetings and building commitment and establishing good cooperation between internal and external parties in improving the quality of schools, and also making yourself a professional trainer in developing the abilities of teaching staff and educational staff so they can carry out their duties and responsibilities well to improve the quality of schools through management carried out by the school principal.